2004
DOI: 10.1002/pbc.20285
|View full text |Cite
|
Sign up to set email alerts
|

Upstream CpG island methylation of the PAX3 gene in human rhabdomyosarcomas

Abstract: PAX3 CpG island methylation appears to distinguish embryonal subtype of rhabdomyosarcoma from alveolar, and methylation at certain sites within this CpG island is inversely correlated with PAX3 expression. In addition to exemplifying developmental dysregulation, methylation of PAX3 has potential in the development of an epigenetic profile for the diagnosis of rhabdomyosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…HIC1, RASSF1A, and PRKCDBP were previously reported as hypermethylated genes in lung cancer Dammann et al 2000;Xu et al 2001), but this is the first report indicating that IRF7, ASC, FABP3, and PAX3 are also hypermethylated in lung cancer, although these were previously known as hypermethylated genes in cancers other than that of the lung (Yu et al 2003;Levine et al 2003;Huynh et al 1996;Kurmasheva et al 2005). Receptor-interacting serine-threonine kinase (RIPK) 3, which is part of the same family as RIPK1, which contains a death domain, has never been reported to be hypermethylated in any cancers before our report.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…HIC1, RASSF1A, and PRKCDBP were previously reported as hypermethylated genes in lung cancer Dammann et al 2000;Xu et al 2001), but this is the first report indicating that IRF7, ASC, FABP3, and PAX3 are also hypermethylated in lung cancer, although these were previously known as hypermethylated genes in cancers other than that of the lung (Yu et al 2003;Levine et al 2003;Huynh et al 1996;Kurmasheva et al 2005). Receptor-interacting serine-threonine kinase (RIPK) 3, which is part of the same family as RIPK1, which contains a death domain, has never been reported to be hypermethylated in any cancers before our report.…”
Section: Resultsmentioning
confidence: 75%
“…This gene is hypermethylated in breast cancer (Levine et al 2003). Paired box gene 3 (PAX3) was recently reported to be hypermethylated in rhabdomyosarcoma (Kurmasheva et al 2005). This gene is a member of the paired box (PAX) family of transcription factors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the IGF2 cluster has a gametic DMR located 2 kb upstream from the H19 nc RNA promoter, which is methylated only in the paternal gamete and is maintained thereafter in all somatic tissues 41. Kurmasheva et al 42 suggested PAX3 gene methylation may be correlated with gene inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike normal muscle, a CpG island within PAX3 is hypermethylated in the majority of ERMS but not in most ARMS. This CpG methylation is inversely correlated with PAX3 expression [51].…”
Section: Pax3 Gene In Embryogenesis and Cancermentioning
confidence: 99%